Analysis of Factors Affecting Indonesia's Economic Growth: The Impact of Inflation and Distribution of Zakat, Infaq, Shodaqoh (ZIS) Funds to Amil Zakat Institutions (LAZ) - Legowati, Diah Ayu; Yastika, Astri; Nuryadin, Deni (Digital Business: Tren Bisnis Masa Depan, 2024)
This research aims to analyze the influence of inflation and ZIS distribution funds on economic growth in Indonesia in January 2017 - June 2021. The research method used in this research is quantitative. The data collection technique used in this research is documentation with data sources obtained from reportspublishedvia the Bank Indonesia (BI) website, the Central Statistics Agency (BPS), and the BAZNAS Monthly Financial Report for January 2017 - June 2021. The data analysis technique used in this research is multiple linear regression analysis and the calculation tool used is eviews-12 . The research results show that partially the inflation variable has a significant influence on economic growth in Indonesia. Furthermore, the ZIS fund distribution variable also has a significant influence on economic growth in Indonesia. Then, simultaneously the variables inflation and ZIS distribution also have a significant influence on economic growth in Indonesia.